The analysis of an electric machine with a smooth air-gap allowing for all winding mmf harmonics. - Van der Merwe, Frederik Strauss (Stellenbosch : Stellenbosch University, 2012)
Thesis (Ph.D.) -- University of Stellenbosch, 1975.